In Situ Remaining Creep Life Prediction Methods for Modified 9Cr-1Mo Steel - NAKASONE, Yuji (Transaction of Japan Society of Spring Engineers, 2023)
The present paper proposes new remaining creep life prediction methods that can be used in situ as an in-service inspection tool for the condition-based monitoring of high-temperature structural components of modified 9Cr-1Mo steel. The methods were based on two types of the modified theta methods and the combination of the modified theta and modified omega methods and were applied to creep deformation data during creep tests made at different applied stress levels at 823K and 923 K in air. Creep lives were predicted by the proposed three methods at arbitrary time in the continuous measurement of deformation during the creep tests. The results show that the combination of the modified theta and modified omega methods gives the most accurate prediction of creep rupture time at the two levels of test temperature for different applied stress levels.